2016
DOI: 10.1111/jbi.12806
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and drivers of soil microbial communities in Tibetan alpine and global terrestrial ecosystems

Abstract: Aim Soil microorganisms play key roles in regulating many important ecosystem processes. However, our understanding of the patterns and drivers of soil microbial communities remains limited. This study aims to test the hypothesis that edaphic factors are more important in explaining variations in soil microbial communities than climatic and biotic factors, as soils directly provide substrates and environment for soil microbial communities. Location Tibetan alpine grasslands and global terrestrial biomes. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 51 publications
(132 reference statements)
10
52
1
Order By: Relevance
“…It has been demonstrated that precipitation was a key limiting factor regulating vegetation production [ Yang et al ., ] and soil organic C density [ Yang et al ., ]. The spatial variations of microbial biomass and microbial community composition in Tibetan alpine grasslands were also reported to be regulated by the precipitation [ Chen et al ., ]. Our additional analyses found significant effects of precipitation on soil C:N ratio (Figure S8a) and the stoichiometric imbalance between microbial decomposers and their resources ( S C:N / M C:N ; Figure S8b).…”
Section: Discussionmentioning
confidence: 84%
“…It has been demonstrated that precipitation was a key limiting factor regulating vegetation production [ Yang et al ., ] and soil organic C density [ Yang et al ., ]. The spatial variations of microbial biomass and microbial community composition in Tibetan alpine grasslands were also reported to be regulated by the precipitation [ Chen et al ., ]. Our additional analyses found significant effects of precipitation on soil C:N ratio (Figure S8a) and the stoichiometric imbalance between microbial decomposers and their resources ( S C:N / M C:N ; Figure S8b).…”
Section: Discussionmentioning
confidence: 84%
“…Chen et al . () also found that environmental variations accounted for a greater portion of the variation in soil microbial community in Tibetan alpine grasslands than did biotic factor.…”
Section: Discussionmentioning
confidence: 99%
“…b,c), supporting our second hypothesis. The alpine steppe was reported to have a lower GPB biomass, GNB biomass, fungal biomass, AMF biomass and Act biomass but a higher F:B ratio than the alpine meadow (Chen et al ., ). Thus, an interesting question arose concerning how changes in the soil microbial communities between these two grassland systems could induce microbial C:N:P stoichiometric flexibility over a broad geographical scale.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we tested the following hypotheses: (1) microbial C:N:P stoichiometry is larger in the alpine steppe than in the alpine meadow, whereas soil C:N:P stoichiometry is lower in the alpine steppe than in the alpine meadow because the alpine meadow has better environmental conditions (e.g. in terms of soil organic carbon, soil moisture, soil acidity and soil texture) (Yang et al ., ) than the alpine steppe, which benefit the growth of soil microbes (Chen et al ., ); and (2) variations in the microbial C:N:P stoichiometry are primarily related to shifts in soil microbial communities and are less related to abiotic factors over a broad geographical scale because microcosm studies have demonstrated that plasticity in microbial biomass stoichiometry is related to changes in the structure of soil microbial communities (Fanin et al ., ; Heuck et al ., ).…”
Section: Introductionmentioning
confidence: 97%